2005
DOI: 10.1161/01.hyp.0000167152.98618.4b
|View full text |Cite
|
Sign up to set email alerts
|

Management of Prehypertension

Abstract: A 58-year-old woman is evaluated by her primary care physician, her gynecologist, or at employee health. On 2 separate occasions, duplicate seated blood pressure (BP) measurements average 132/84 mm Hg. She is informed that she has "prehypertension." At her last check-up in 2002, she had a similar reading but was told she had normal BP.The BP category "prehypertension" was first introduced by the Seventh Joint National Committee on Prevention, Detection, Evaluation, and Treatment of High Blood Pressure (JNC-7) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(47 citation statements)
references
References 64 publications
0
41
0
6
Order By: Relevance
“…Overweight and obesity are related to a number of health consequences, including type two diabetes, coronary heart disease, stroke, hypertension, gallbladder disease, and certain types of cancer, sleep apnea, psychosocial disturbances and osteoarthritis (8). Some recent studies also revealed that overweight and obesity are the main risk factors for prehypertension (9)(10)(11)(12). There are few data on the epidemiology of overweight and obesity in the county of China.…”
Section: Introductionmentioning
confidence: 99%
“…Overweight and obesity are related to a number of health consequences, including type two diabetes, coronary heart disease, stroke, hypertension, gallbladder disease, and certain types of cancer, sleep apnea, psychosocial disturbances and osteoarthritis (8). Some recent studies also revealed that overweight and obesity are the main risk factors for prehypertension (9)(10)(11)(12). There are few data on the epidemiology of overweight and obesity in the county of China.…”
Section: Introductionmentioning
confidence: 99%
“…18 By lowering the mean SBP in a population by 3.5 mmHg, cardiovascular mortality could be reduced by 26%. 8,24,25 Therefore; our study group could represent a population at increased risk for systolic hypertension and cardiovascular disease and should be monitored closely.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the reference values of the VII Joint National Committee (JNC-7), the students classified as normotensive presented SAP < 120 mmHg and DAP < 80 mmHg, and as pre-hypertensive those with SAP ≥ 120 mmHg and/or DAP ≥ 80 mmHg, respectively 8 . The highest value of systolic or diastolic BP establishes the diagnosis 9 .…”
Section: Blood Pressure Measurement (Bp)mentioning
confidence: 99%